Promoting creative autonomy support in school music education: An intervention study targeting interaction - Hendriks, Linda H.; Steenbeek, Henderien W.; Bisschop Boele, Evert H.; van Geert, Paul L. C. (Frontiers in Education, 2023)
The notion of autonomy in Self-Determination Theory is at the core of intrinsically motivated learning, and fulfilment of the need for autonomy is essential for thriving at school. Therefore teacher-provided autonomy support has grown into a key concern in educational research. In the present study into primary school music education, the notion of creative autonomy support is introduced, building on Stefanou et al. (2004). Research into autonomy support is typically focused on verbal interaction. However, from an enactive perspective, teachers’ gesturing, bodily movement, facial expression and musical action form an integral part of the socially situated interaction in music lessons, inherently involving autonomy support. In the present study, a distinction is made between creative verbal autonomy support and creative musical and non-verbal autonomy support. Applying a process-based time-serial methodology, rooted in a Complex Dynamic Systems and Enactive perspective, the effects of an intervention with Video Feedback Coaching for teachers were investigated. Video data of one hundred and five music lessons of eighteen teachers (intervention and control condition) from six primary schools was gathered, to examine teachers’ creative autonomy support at both the individual and group level. The findings show that teachers in the intervention condition, compared to the control group, achieved a meaningful increase in their ability to offer creative autonomy support verbally. Teachers also showed development for the non-verbal and musical aspects of offering creative autonomy support. However, particularly for offering higher-level creative autonomy support in the non-verbal and musical mode, significant results were found for less than half of the intervention teachers. These results underline the importance of embracing and studying autonomy support and both its verbal and bodily dimensions as an integral part of music teaching, aimed at emergence of students’ musical creativity, in primary school music education and in teacher training. We explain how these results might be relevant for autonomy enhancing musical activities in vulnerable groups.